Measuring the Boiling Point of the Vacuum of Quantum Electrodynamics - (:unkn) unknown (American Physical Society, 2019)
It is a long-standing nontrivial prediction of quantum electrodynamics that its vacuum is unstable in the background of a static, spatially uniform electric field and, in principle, sparks with spontaneous emission of electron-positron pairs. However, an experimental verification of this prediction seems out of reach because a sizeable rate for spontaneous pair production requires an extraordinarily strong electric field strength vertical bar E vertical bar of order the Schwinger critical field, E-c = m(e)(2)/e similar or equal to 1.3 x 10(18) V/m, where m(e) is the electron mass and e is its charge. Here, we show that the measurement of the rate of pair production due to the decays of high-energy bremsstrahlung photons in a high-intensity laser field allows for the experimental determination of the Schwinger critical field and, thus, the boiling point of the vacuum of quantum electrodynamics.